Building maintenance audit with the [AID] of [GIS] / Norfarahiah Azhar - Azhar, Norfarahiah (2019)
Maintenance is important in maintaining a building condition in order to avoid unnecessary cost and to avoid accident. Nowadays, most of the building does not go through maintenance due to the high cost for maintenance. The aim for this research is to determine the condition of the building whether it can be maintained or not by creating a database for the maintenance data, visualised the data and also mapping the defect of the building. The research started from collecting the inspection data to be used in database creation. Then, it is being processed in ArcMAP software to be visualised and also to map the defect for the building. The final product of this research is the map of the defect in 2D. It is more convenient compare to the conventional method as the information of the defect can be obtained in the map. It can reduce the time constraint and help to reduce the time for the maintenance team to take action according to the condition of the building.